Single Stage RF Amplifier with High Gain for 2.4GHz Receiver Front-Ends - Achmad Munir; Biru Tutur Ranum (Universitas Ahmad Dahlan, 2014)
The paper deals with the numerical and experimental development of single stage radio frequency (RF) amplifier with high gain for 2.4GHz receiver front-ends. The work is motivated by the increasing demand of high-gain receiver amplifier in low-cost especially for wireless local area network (WLAN) application. Prior hardware realization and experimental characterization, the proposed amplifier which uses a single RF transistor of BFP420 type is numerically designed using ADS® software to satisfy the required specification. To obtain the impedance matching at ports of amplifier, microstrip lines are employed at the input and output ports. The prototype of amplifier is realized by use of a dielectric substrate of glass-reinforced epoxy lamination (FR4) board which has thickness of 0.762mm and relative permittivity of 4.3. The prototype is then experimentally characterized and demonstrates the gain of 13.35dB at frequency of 2.4GHz with the noise figure of 3.33dB, the input and output voltage standing wave ratio (VSWR) of 2.08 and 2.55, respectively.